Removal of Sediment and Nutrient from Stormwater Using Geotextile and Mix-medium in a Laboratory Scale Catch Basin Insert - Anwar, Faisal; Chen, Weizhuang; Alam, Md Zahanggir (2020)
The urban stormwater runoff carries significant amount of sediments and nutrients and discharges into the nearby water bodies. Among the best management practices (BMPs), catch basin insert (CBI) is a promising technology that can remove stormwater pollutants at source. We have investigated the one-stage CBI to remove gross pollutants from stormwater but it was unable to remove dissolved pollutants. Next, we have tested a mix-medium of biochar and alum sludge in batches to remove nutrients from water. In this study, a modified two-stage CBI was experimented in a laboratory column using non-woven geotextile and a mix-medium of biochar and alum sludge. A synthetic stormwater composed of sediments (0-300µm) and nutrients (NH3-N, NO3-N, NO2-N, PO4-P) (1-5mg/L) was pumped into the column at flowrate of 5-10 mL/min. The column effluent was collected at predefined time interval and measured for total suspended solid (TSS) and nutrient concentrations. The results revealed that TSS removal was higher (>90%) in coarse sediments (>150 µm) and the nutrient removal was significant except for NO3-N. The PO4-P removal (98-100%) was found highest followed by NH3-N (97-98%) and NO2-N removal (94-96%). However, the flow rate did not show significant effect on nutrient removal using the mix-medium.